PENINGKATAN MOTIVASI DAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN KOOPERATIF BERBASIS QUIZIZ PADA PEMBELAJARAN IPAS - Perdana Miftachul Hudaa; Yudi Hartono; Karni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Students' learning motivation is considered to be still low, one of the reasons is that learning models and media are less enjoyable. Strategy for overcoming existing problems by practicing the quiziz-based cooperative learning model. This research aims to find out how the use of the Quizizz-based cooperative learning model can increase student motivation and learning outcomes in studying science. The research method used is Classroom Action Research (PTK). The sample in this research was 14 students. The research results showed that in cycle I, an average of 57.5% was classified as being in the medium category, and data from student observations in cycle II, an average of 72.5% was in the good category. Student learning outcomes also show improvement. This is shown by observation data from cycle I: completeness of learning outcomes was 69%. However, when cycle II actions were carried out, student learning outcome data increased by 78%. Keywords: Learning models, student motivation, learning outcomes